Implementation of Mosque Management in Improving Community Religiusity - Ahmad Hanafi MTD; Soiman Soiman (Al-Fikru: Jurnal Ilmiah, 2023)
Mosque should play a role in increasing the religiosity of the people, but improper management certainly cannot fulfill this expectation. Management must pay attention to the needs and developments of the times, without ignoring the main things of the function of the mosque. This study aims to analyze mosque management practices to increase the religiosity of Bandar Selamat villagers. This research was conducted at the Al-Huda mosque, Bandar Selamat Village. In this study, the authors used qualitative research methods, with a phenomenological approach using descriptive analytical techniques. The results of the study explained that the management of the Al-Huda Mosque strengthened the trust of the people of Bandar Selamat Village with several activities such as the existence of a ta'lim assembly, yasinan, Al-Qur'an educational park and Islamic syiar. The program for simplification of religious holidays has been well managed. In this case the mosque management will form mosque youth with future mosque youth to invite the community to strengthen the faith of the Kelurahan community in Bandar Selamat. The results of this research can certainly be a basis for administrators of other mosques to carry out the same development.